Effects of sleep restriction, sleep inertia, and overload on complex cognitive performance before and after workload transition: a meta analysis and two models. (September 2014) - Wickens, Christopher D.; Laux, Lila; Hutchins, Shaun; Sebok, Angelia
We describe performance models and meta-analytic data in a period before and after an unexpected workload transition typical, for example, of a catastrophic automation failure, experienced by a fatigued operator. We first present meta-analytic findings on the effects of sleep restriction and sleep inertia on the complex cognitive performance that might typify such a "failure response". We then present a workload overload task management model whose parameters are based on meta-analyses, relevant to predicting multi-task performance in the post-transition phase performance (independent of sleep disruption effects). We cite the lack of research intersecting these two areas.